Managers look to the social network to seek information - Mckenzie M.L. (Information Research: An International Electronic Journal)
Introduction. The purpose of this study was to explore how managers selected individuals to serve as information sources. The social context of a for-profit business environment offered opportunity to study information seeking among interacting line managers. Method. The qualitative methods of social network mapping and interview were used to capture the data. The study was conducted within a stand-alone business unit of a major US-based corporation. A total of 22 line-managers participated in the study. Analysis. Content analysis was selected as the data analysis technique. The elements of interest were the themes within the data. Open coding was used to interrogate the data to ensure a systematic approach so that future researchers can replicate the process. Results. Relationship, more than knowledge, can be the reason a line-manager is sought as an information source. In addition to relationship, an individual managers knowledge, communication behaviour, cognitive style, and cognitive ability play an influencing role in being selected as an information source. Conclusion. The non-hierarchical flow of information among managers and the reasons managers seek others as information sources further differentiates line-managers as a unique information user group